Impact of a new levonorgestrel intrauterine system, Levosert®, on heavy menstrual bleeding: results of a one-year randomised controlled trial. (June 2014) - Mawet, Marie; Nollevaux, Fabrice; Nizet, Dominique; Wijzen, Fabienne; Gordenne, Valérie; Tasev, Niso; Segedi, Dimitrije; Marinescu, Bogdan; Enache, Andreea; Parhomenko, Vadim; Frankenne, Francis; Foidart, Jean-Michel
Abstract Objective To evaluate a new levonorgestrel-releasing intrauterine system (LNG-IUS) called Levosert® for the treatment of heavy menstrual bleeding (HMB) in comparison to the reference product Mirena®. Methods A multicentre, randomised, controlled trial, in non-menopausal women diagnosed with functional HMB (defined as menstrual blood loss [MBL] ≥ 80 mL) randomised to either Levosert® or Mirena® and followed for up to one year. MBL was evaluated using a validated modified version of the Wyatt pictogram. Results A total of 280 women were randomised (141 to Levosert® and 139 to Mirena®). During the one-year treatment period, both Levosert® and Mirena® dramatically decreased MBL and increased haemoglobin and ferritin levels. There were no statistically significant differences between Levosert® and Mirena® regarding any of the parameters evaluated during the study. Similar bleeding patterns were observed in both groups. Levosert® was inserted with the same ease as Mirena®. Both treatments were associated with identical expulsion rates and no perforations occurred in either treatment group. Conclusion Levosert®, a new LNG-IUS designed to release the same daily amount of LNG as Mirena®, is highly effective in the treatment of HMB. No differences were observed between Levosert® and Mirena® regarding all evaluated outcomes, including safety profile.